Advanced platelet‐rich fibrin and freeze‐dried bone allograft for ridge preservation: A randomized controlled clinical trial. Issue 4 (23rd April 2018) - Clark, Daniel; Rajendran, Yogalakshmi; Paydar, Sarmad; Ho, Sunita; Cox, Darren; Ryder, Mark; Dollard, John; Kao, Richard T.
Abstract: Background: Advanced platelet‐rich fibrin (A‐PRF) is an autogenous blood product with applications in dento‐alveolar surgery. However, there is minimal information regarding its optimal clinical application or efficacy. The aim of this multi‐arm parallel randomized controlled clinical trial was to evaluate the efficacy of A‐PRF alone or with freeze‐dried bone allograft (FDBA) in improving vital bone formation and alveolar dimensional stability during ridge preservation. Methods: Forty patients requiring extraction of non‐molar teeth and replacement with dental implants were randomized into one of four ridge preservation approaches: A‐PRF, A‐PRF+FDBA, FDBA, or blood clot. A‐PRF was prepared at 1, 300 rpm for 8 minutes. Non‐traumatic extractions and ridge preservation was performed. After an average of 15 weeks healing, bone core samples were harvested at the time of implant placement for micro‐CT and histomorphometric analysis. Ridge dimensions were measured immediately after extraction and before implant placement. Results: Significantly greater loss of ridge height was noted in the blood clot group (3.8 ± 2.0 mm) compared to A‐PRF (1.8 ± 2.1 mm) and A‐PRF+FDBA (1.0 ± 2.3 mm) groups ( P  < 0.05). No significant differences in ridge width reduction were noted between groups. Significantly more vital bone was present in the A‐PRF group (46% ± 18%) compared to the FDBA group (29% ± 14%) ( P  < 0.05). Bone mineral density was significantly greater in the FDBA group (551 ± 58 mg/cm 3 ) compared to blood clot (487 ± 64 mg/cm 3 ) ( P  < 0.05). Conclusions: This study demonstrates A‐PRF alone or augmented with FDBA is a suitable biomaterial for ridge preservation. This study represents the first randomized controlled clinical trial comparing A‐PRF with and without FDBA to FDBA alone for ridge preservation.